Plankton and macroinvertebrate dynamics in the Khakhea"“Bray transboundary aquifer region - Mungenge, Chipo Perseverance (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Temporary wetlands are prevalent in semi"“arid and arid climates across the globe and harbour unique faunal assemblages that significantly contribute to regional aquatic biodiversity. This study aims to enhance our understanding of the ecological dynamics of temporary wetland ecosystems, focusing on plankton dynamics, large branchiopod diversity, trophic dynamics, water quality and the impacts of freshwater salinisation in temporary pans in the Khakhea Bray Transboundary aquifer region in the North west Province, South Africa. This body of work represents field, laboratory and writing components which span the period May 2021 to December 2023. The results from this study revealed seasonal patterns in plankton diversity with a winter peak in phytoplankton diversity dominated by Zygnematophyceae species, while Chlorophyceae were dominant in summer. Zooplankton diversity was high in summer as compared to winter, with both Rotifera and Copepoda dominant in both seasons. Six large branchiopod species were found in the region, and three of these were new distribution records for the North west Province, including the first record of Phallocryptus spinosa in the salt pan that was sampled in summer. Large branchiopod diversity was mainly influenced by water temperature and phosphorous in summer, while sediment sodium influenced the diversity in winter. The stable isotope analyses used to determine trophic dynamics in these temporary pans revealed that the food web had four trophic levels, with the top predators being the notonectids Anisops sp. The dominant consumers were predatory insects such as Sigara sp., Anisops sp., Lestes sp., Rhantus sp. and Cybister sp. adults and larvae, as well as detritivorous Tomopterna sp. tadpoles. High trophic niche overlaps were found between the notonectids and the dytiscids. These temporary pans are susceptible to anthropogenic impacts, and disturbed pans were found to have elevated pH, ammonium, phosphates and dissolved oxygen compared to the undisturbed pans. A strong positive relationship was observed between chl"“a and temperature, pH, dissolved oxygen, phosphates and ammonium. Chlorophyll"“a concentration increased as surface area and the distance from kraals, buildings and latrines decreased. Freshwater salinisation was found to cause notable shifts in abiotic factors and benthic phytoplankton communities, favouring the proliferation of saline"“tolerant diatom species at the cost of more sensitive taxa. The study also revealed that in interaction with salinisation, time also exerted a notable influence on shaping the benthic phytoplankton community. Salinity levels of 2.5 ppt and above led to significant decreases in emergent taxa richness and abundance, with Spinicaudata and Ostracoda being the most sensitive taxa to high salinities. There was a limited effect on community hatching phenology dynamics from salinity. This suggests that the main impact of salinisation in these systems will be reductions in hatching success and, hence, reduced recruitment. The study highlights the vulnerability of temporary pan ecosystems to anthropogenic influences and the complexities of interactions of organisms and the environmental conditions in these systems.
Keywords: Vernal pools Africa, Southern; Water quality; Crustacea; Freshwater salinization; Food chains (Ecology)